2022
DOI: 10.1007/s11409-021-09287-3
|View full text |Cite|
|
Sign up to set email alerts
|

Association and dissociation between judgments of learning and memory: A Meta-analysis of the font size effect

Abstract: The font size effect is a metamemory illusion in which larger-font items produce higher judgments of learning (JOLs) but not better memory, relative to smaller-font items. We conducted meta-analyses to determine what is currently known about how font size affects JOLs and memory accuracy. In addition, we implemented both univariate and multivariate meta-regressions to isolate the moderators of JOL effects and memory effects. The results revealed a small-to-moderate effect of font size on JOLs. There was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…Unlike many previous studies that showed no significant relationship between font size and memory (e.g., Mueller et al, 2014;Rhodes & Castel, 2008;Susser et al, 2013), this study found that large-font words had higher memory recall than small ones. This result was consistent with recent studies and meta-analyses (Chang & Brainerd, 2022;Halamish, 2018;Luna et al, 2018;2019;Undorf & Zimdahl, 2019). In both experiments, this study demonstrated reliable effects of JOLs and memory recall increasing with font size.…”
Section: The Relationship Between Font Size and Memorysupporting
confidence: 93%
See 4 more Smart Citations
“…Unlike many previous studies that showed no significant relationship between font size and memory (e.g., Mueller et al, 2014;Rhodes & Castel, 2008;Susser et al, 2013), this study found that large-font words had higher memory recall than small ones. This result was consistent with recent studies and meta-analyses (Chang & Brainerd, 2022;Halamish, 2018;Luna et al, 2018;2019;Undorf & Zimdahl, 2019). In both experiments, this study demonstrated reliable effects of JOLs and memory recall increasing with font size.…”
Section: The Relationship Between Font Size and Memorysupporting
confidence: 93%
“…In both experiments, this study demonstrated reliable effects of JOLs and memory recall increasing with font size. In some details of the experimental design, our experiments coincided with the factors summarized by Chang and Brainerd (2022). These factors are conducive to observing that large fonts have a better memory recall than small ones, such as using a reasonable range of font sizes, learning unrelated word lists, adopting an immediate JOL task, and having brief study time.…”
Section: The Relationship Between Font Size and Memorymentioning
confidence: 63%
See 3 more Smart Citations